Reconstruction of Law and Policy : Rights and Environment Problem in Northern East Java -Pekalongan - Kuat Puji Prayitno; Icuk Rangga Bawono (Faculty of Law, Universitas Pekalongan, 2022)
Many populations of society in Pekalongan live in this kind of areas and are vulnerable to the risks of coastal flooding, wetland loss, shoreline retreat and loss of infrastructure. Land subsidence is defined as the gradual vertical movement of the earth surface due to the subsurface movement of the earth materials.This research is prior to explain about the rights, environment law, law and reconstruction using juridical normative methodology. In the end, this research describe how important to promote fundamental rights for coastal society in pekalongan. The approach method used the doctrinal legal research.Many populations of society in Pekalongan live in this kind of areas and are vulnerable to the risks of coastal flooding, wetland loss, shoreline retreat and loss of infrastructure. Land subsidence is defined as the gradual vertical movement of the earth surface due to the subsurface movement of the earth materials.This research is prior to explain about the rights, environment law, law and reconstruction using juridical normative methodology. In the end, this research describe how important to promote fundamental rights for coastal society in pekalongan. The approach method used the doctrinal legal research.